KAJIAN MODAL SOSIAL, DUKUNGAN SOSIAL, DAN KETAHANAN KELUARGA NELAYAN DI DAERAH RAWAN BENCANA - Sunarti, Euis; Fitriani, Fitriani (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The objectives of this study were to analyze the correlation among family’s strengths, social capital, and social support of fisherman’s families and to differ those variables in the two types of fishermen groups (Juragan and Janggol). Study design was cross sectional; samples of the study were 80 families (53 Juragan and 27 Janggol) selected by using proportional random sampling method, and conducted in Pangandaran District, Ciamis Regency in May 2009. The study indicated that most of samples categorized as small size family (family members approximately 4 people) and had length of formal education less than 9 years. The average of family asset owned by Juragan was twice than that of Janggol. The first variable, Family strengths, consisted of physical, social, and psychological components. There was no significant difference in psychological and social strengths between Juragans and Janggols; however regarding the physical strengths, Juragan had higher level than Janggols. It was found that Juragan had higher average per capita income and family asset than Janggol. The next variable, social support comprised emotional, economic, and information support. Fishermen families received social support from the extended family, neighbors, and community agencies/governments, in terms of a sense of security and empathy, financial assistance and information about weather changes, in this matter, there was no difference between Juragan and Janggol. The last variable, social capital was divided into local associations and community characters. The number of local associations joined by the samples ranged from one to four. Generally, samples actively participated in every meeting conducted by the associations, but the number of Janggol who did not feel the benefit of such associations was three times as much as Juragan. Moreover, community characters were divided into the trust, solidarity, and morale. At high categorized, the Janggols had twice higher solidarity than the Juragans. Different test showed that Juragan involved in much more associations than Janggols. Correlation test showed that samples who had better social support possessed a better family social capital (particularly in participation in local associations) and better family income and consequently possessed better family physical strength, while samples who had better social capital had better family physical strengths. The result of study indicates the importance of social capital and social support improvement for fishermen’s family as part of the Program for Strengthening and Empowering the Family conducted by both BKKBN (National Agency for Population and Family Planning) and DKP (Ministry of Marine and Fisheries).